2021
DOI: 10.1017/s0007114521001768
|View full text |Cite
|
Sign up to set email alerts
|

Urinary sodium excretion and the risk of CVD: a community-based cohort study in Taiwan

Abstract: Urinary sodium excretion is a potential risk factor for cardiovascular diseases (CVD). However, the underlying biological mechanisms and effects of salt sensitivity are unclear. The purpose of this study was to characterize the relative contribution of biological factors to the sodium-CVD association. A total of 2112 participants were enrolled in this study. Structured questionnaires and blood and urine samples were obtained. Twenty-four-hour sodium excretion was estimated using a single overnight urine sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
1
0
0
Order By: Relevance
“…Furthermore, an MR study investigating the impact of urinary sodium on cardiovascular risk factors, ischemic stroke, and heart failure (HF) demonstrated that higher levels of urinary sodium were associated with an elevated risk of both HF and global ischemic stroke ( 34 ). Consistent with our own findings, a cohort study conducted in Taiwan revealed a significant association between increased urine sodium excretion and a higher risk of CVD, particularly stroke ( 35 ). However, a Finnish cohort study reported contrasting results, finding no significant correlation between urinary sodium levels and major adverse coronary events in men with HF ( 36 ).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, an MR study investigating the impact of urinary sodium on cardiovascular risk factors, ischemic stroke, and heart failure (HF) demonstrated that higher levels of urinary sodium were associated with an elevated risk of both HF and global ischemic stroke ( 34 ). Consistent with our own findings, a cohort study conducted in Taiwan revealed a significant association between increased urine sodium excretion and a higher risk of CVD, particularly stroke ( 35 ). However, a Finnish cohort study reported contrasting results, finding no significant correlation between urinary sodium levels and major adverse coronary events in men with HF ( 36 ).…”
Section: Discussionsupporting
confidence: 90%